Slovakisms and Bohemisms in Spanish - Ulašin, Bohdan (Eslavística Complutense, 2011)
The article collects and analyzes from the etymological, semantic and formal point of view the words of Slovak and Czech origin in the Spanish language.
Keywords: slovakism; bohemism; loanword; calque; eponym